Desarrollo de una aplicación web para el control de pasantías o prácticas pre-profesionales de la Universidad Nacional de Loja. - Arrobo Ajila, Jonathan Bladimir (2016)
Focused on the development of the university , one of the main needs met, is the lack of an application system that allows teachers to keep the control of pre-professional practices as well as for students to have a daily register of their activities, the hours they are doing as practices and the creation of information based on the registered activities. Control practices currently performed is manual, the documentation of reports submitted by students is lost, no studies of students who have completed their practices, it is difficult to move to the place for surprises visitors and there is no systemized among all races of the National University of Loja process. Currently there are innovative tools for developing an application that allows to solve the process control practices and to have the information in a computerized system, considering this issues we proceed to create the “Development of a web application for the control of pre-professional internships or practices at nacional de loja university”, The methodology, used is the RUP, which requires us to divide the process into 4 phases: analysis, design, development and implementation. People immerse in this project are coordinators, teachers, rector of the institution and students from different careers that belong to the Nacional de Loja University. To obtain information, the interview techniques, survey and observation sheet was applied; obtaining as a result the system requirements which subsequently were known to the sample population so that analysts support the implementation of the first objective. Subsequently it was designed various diagrams that requires methodology to facilitate the understanding to developers so in that way to continue development of the application, giving the fulfillment of the second objective; during the development of the application it was made the connection to the Web Service that provides Academic Management System (SGA)of the Universidad Nacional de Loja. It was useful to us to consume the information of teachers and students. To successfully complete the development of this project the testing of the system was made to conclude the third objective. To meet the fourth objective of the implementation, the application is stored into the server of the “Nacional de Loja “University. For the training of the user it was it was chosen some students per career where users are involved explaining them how the application works.